Perceived social support according to the type and number of addictions - Alexander Tomei; Joseph Studer; Gerhard Gmel (PLoS ONE, 2025)
Background Addiction is very closely related to social determinants. It can be an outcome of the excessive consumption pushed by society and be protected against by society’s many positive dimensions. The main objectives of the present paper are to examine whether perceived social support (PSS) – the perceived availability of others to provide us assistance when needed – varies (a) according to different types of addiction (i.e., gambling, gaming, alcohol, cannabis, and nicotine), and (b) according to the presence of multiple addictions. Methods A sample of 5654 male emerging adults (mean age = 21.34 years old) completed a questionnaire that included a scale for measuring PSS and several screening tools used to identify addictive behaviors like gambling, gaming, and the consumption of alcohol, cannabis, or nicotine. Results Compared to a non-addicted control group and to peers with alcohol, cannabis or nicotine disorder, male emerging adults with gambling or gaming addiction reported the lowest levels of PSS. Moreover, these findings showed that PSS decreased among male emerging adults with multiple addictions. Conclusion Our results suggest that young men with gambling and gaming disorders may be at a greater risk of social isolation and loneliness and, thus, of experiencing deteriorations in their physical and mental health.